Reporting from Iraq : on the ground in Fallujah - Cooper, Candy J., 1955- (X-books. Total war., 2020)
Briefly follows the experiences of reporter Anne Garrels reporting on the ground with American troops as they launch their assault on the city of Fallujah during the War in Iraq in the early 2000s. Highlights what Garrels saw and noticed about the American troops she followed into the battle.